COVERAGE OF SPEECH, COMMUNICATION, READING AND WRITING SKILLS IN THE FIRST STEP CURRICULUM - Shahodat Khudoyberganova (Journals Park Publishing, 2022)
In this article, the special features, importance and goal tasks of speech, communication, reading, writing skills in the "First Step" educational program, as well as expected results in the areas of small speech and language, fine motor skills of fingers and hands are highlighted.
Keywords: competence, child competence, fine motor skills, speech, speaker, speech culture.